GAMBARAN PENGETAHUAN IBU TENTANG PENCEGAHAN CORONAVIRUS DISEASE 2019 (COVID-19) PADA ANAK DI DESA LAMPOH KEUDE ACEH BESAR - Irma Andriani; Yuli Riska; Fauziah Fauziah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2020)
Coronavirus Disease 2019 (Covid-19) is a global pandemic, where one of the provinces in Indonesia experiencing local transmission is Aceh. Children can become victims of invisible Covid-19 transmission because it is transmitted by their families. Therefore, knowledge of mothers is very much needed in preventing Covid-19 in children. This study aims to describe the knowledge of mothers about preventing Covid-19 in children in Lampoh Keude Village, Aceh Besar. This research is descriptive quantitative with cross sectional study design. The population in this study were all mothers who had children in Lampoh Keude Village, Aceh Besar. Sampling was done by total sampling technique so that 45 respondents were obtained. Data collection tool in the form of a questionnaire distributed to respondents with 16 questions. The results showed that mother's knowledge about preventing Covid-19 in children was in the high category of 27 respondents (60%), mother's knowledge about prevention of Covid-19 in children based on early detection and control aspects was high, with 27 respondents (60%), based on aspects of administrative control in the low category are 24 respondents (53.3%), and based on environmental control aspects in the high category are 23 respondents (51.1%). Based on the results of this study, it is recommended for mothers to increase knowledge about preventing Covid-19 in children in order to avoid transmission of the Covid-19 virus and create a healthy and prosperous social life.Keywords: Knowledge, Mother, Covid-19 Prevention